DOI: 10.24834/isbn.9789178773022
|View full text |Cite
|
Sign up to set email alerts
|

Locating place, crime and the fear of crime: methodological and theoretical considerations

Abstract: Much previous research on the fear of crime has focused on why some individuals, with certain characteristics, experience more or less fear of crime than others. However, there is also a growing body of research examining the role that the neighbourhood context in which individuals reside plays in shaping such feelings and perceptions. At the same time, less research has been directed at understanding why certain small-scale micro-places evoke feelings of unsafety and fear of crime. The aim of this dissertati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 138 publications
0
1
0
Order By: Relevance
“…The comparable size of AuNPs to enzymes, combined with their unique physicochemical properties, facilitates efficient electronic coupling processes. Studies in this area have shown that gold nanoparticles not only serve as the enzyme carriers but also actively participate in aligning enzymes on their surfaces and directly wiring the redox center to the electrode [90][91][92][93][94]. Some theories explain this through the large surface area-to-volume ratio of gold nanoparticles.…”
Section: Enzymes On Gold Nanoparticles (Aunps) Modified Electrodesmentioning
confidence: 99%
“…The comparable size of AuNPs to enzymes, combined with their unique physicochemical properties, facilitates efficient electronic coupling processes. Studies in this area have shown that gold nanoparticles not only serve as the enzyme carriers but also actively participate in aligning enzymes on their surfaces and directly wiring the redox center to the electrode [90][91][92][93][94]. Some theories explain this through the large surface area-to-volume ratio of gold nanoparticles.…”
Section: Enzymes On Gold Nanoparticles (Aunps) Modified Electrodesmentioning
confidence: 99%